Effect of GA3 on Growth, Sex Expression and Yield of Watermelon (Citrullus lanatus Thunb.) - Patel, M. V.; Joshi, C. J. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was carried out during the year summer seasons (February to May) of 2019–2021 in at Horticulture Instructional Farm, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar Gujarat (385 506), India to study the effect of GA3 on growth, sex expression and yield of watermelon (Citrullus lanatus Thunb.). Plant growth regulators in cucurbits have shown promise in improving crop growth and productivity by affecting several physiological and developmental processes. The experiment was laid out under randomized block design with three replications and eleven treatments namely T1 (GA3 10 ppm), T2 (GA3 20 ppm), T3 (GA3 30 ppm), T4 (GA3 40 ppm), T5 (GA3 50 ppm), T6 (GA3 60 ppm), T7 (GA3 70 ppm), T8 (GA3 80 ppm), T9 (GA3 90 ppm), T10 (GA3 100 ppm) and T11 (Control). The variety sugar baby is tested under the experiment. The results revealed that length of the main vine (219.91 cm), number of days to first male flower (50.98), sex ratio (8.01), number of fruit vine-1 (2.99), fruit yield vine-1 (5.04 kg) and fruit yield ha-1 (33.25 tone) were highest in treatment T8 (GA3 @ 80 ppm). Thus, foliar application of GA3 80 ppm twice at 2–4 leaf stages and at flowering stage found effective in enhancing the growth, sex expression and yield attributes of watermelon. These findings provide valuable insights into optimizing agricultural practices through the integration of PGRs, improving productivity and profitability, and supporting sustainable watermelon cultivation.